Adsorption of selected azo dyes from an aqueous solution by activated carbon derived from Monotheca buxifolia waste seeds - Nazir, Ruqia; Khan, Muslim; Ur Rehman, Riaz; Shujah, Shaukat; Khan, Mansoor; Ullah, Mohib; Zada, Amir; Mahmood, Nasir; Ahmad, Irshad (Soil and water research, 2020)
In this study, activated carbon derived from Monotheca buxifolia waste seeds was used for the adsorptive removal of a number of selected azo dyes such as Eriochrome Black T (EBT), Remazol brilliant blue (RBB), Remazol yellow (RY) and Remazol brilliant orange (RBO) from an aqueous solution by changing the initial dye concentration, adsorbent dosage, solution pH, contact time and temperature. A Fourier transform infrared spectroscopic analysis of the activated carbon showed the existence of hydroxyls, methyl, methylene, carbonyls, alkane and alkenes groups while the scanning electron microscopic image displayed the gradual formation of cavities and open pores on the surface. The results showed that as the amount of the adsorbent and the shaking time were increased, the removal percentage of the dye increased accordingly. Higher adsorption percentages were observed at a lower dye concentration and temperature in an acidic media at a pH range (1-5). The investigated data were evaluated with the Langmuir and Freundlich adsorption models. The maximum adsorption capacities obtained from the Langmuir model were 112.36, 96.34, 97.65 and 90.91 mg/g for EBT, RBB, RY and RBO, respectively. The results indicated that the electrostatic interaction was the main cause of the adsorption of these anionic azo dyes on the surface of the activated carbon.